What are you grouping for? Grades 3-8 how to guide small groups based on readers - not the book - Wright, Julie; Hoonan, Barry (Corwin literacy., 2019)
Intermediate grade readers don't need to be guided as much as they need to be engaged-and authors Julie Wright and Barry Hoonan have solutions for doing just that using small groups. You'll get practical tools, classroom examples, and actionable steps essential for starting, sustaining, and mastering the management of small groups. This book explains the five teacher moves that work together to support students' reading independence through small group learning-kidwatching, pivoting, assessing, curating, and planning-and provides examples to guide you and your students toward success. This res.